Drug Delivery: Graphene‐Based MicroRNA Transfection Blocks Preosteoclast Fusion to Increase Bone Formation and Vascularization (Adv. Sci. 2/2018). Issue 2 (27th February 2018) - Dou, Ce; Ding, Ning; Luo, Fei; Hou, Tianyong; Cao, Zhen; Bai, Yun; Liu, Chuan; Xu, Jianzhong; Dong, Shiwu
Abstract : In article number1700578, Jianzhong Xu, Shiwu Dong, and co‐workers report the development of a graphene‐based miRNA transfection system that uses a polyethylenimine (PEI) functionalized graphene oxide complex loaded with miR‐7b plasmid. The system efficiently delivers the miR‐7b plasmid into bone marrow macrophases and reduces the expression of target protein dendritic cell‐specific transmembrane protein, specifically targeting cell–cell fusion to block the formation of mature osteoclasts while preserving beneficial preosteoclasts.